The Bible in political debate : what does it really say? - Flannery, Frances; Werline, Rodney Alan, 1961- (2016)
Politicians and pundits regularly invoke the Bible in social and political debates on a host of controversial social and political issues, including: abortion, stem-cell research, gay marriage, the death penalty, separation of church and state, family values, climate change, income distribution, teaching evolution in schools, taxation, school prayer, aid for the poor, and immigration. But is the Bible often used out of context in these major debates? This book includes essays by fourteen biblical scholars who examine the use of the Bible in political debates, uncovering the original historical contexts and meanings of the biblical verses that are commonly cited. The contributors take a non-confessional approach, rooted in non-partisan scholarship, to show how specific texts have at times been distorted in order to support particular views. At the same time, they show how the Bible can sometimes make for unsettling reading in the modern day. The key questions remain: What does the Bible really say? Should the Bible be used to form public policy?
Tracing the Use of the Bible in Colonial Land Claims in North America / Judith H. Newman -- The Bible, Slavery, and Political Debate / Emerson B. Powery -- Women, the Bible, and the Nineteenth Amendment to the U.S. Constitution / Christopher A. Rollston -- pt. 3 Concluding Thoughts. What Is "the Bible"? / Kelley Coblentz Bautch -- Compromise as a Biblical Value / John F. Kutsko -- Notes.
Includes bibliographical references.
Keywords: Bible and politics; Politics in the Bible; Bible and politics; Politics in the Bible